2022
DOI: 10.1177/02697580221079994
|View full text |Cite
|
Sign up to set email alerts
|

Apology–forgiveness cycle in restorative justice, but how?

Abstract: The apology–forgiveness cycle is a simple but powerful process for conflict resolution. Given the prevalence of apology and forgiveness in restorative justice (RJ), the apology–forgiveness cycle may take place. However, there is a lack of theoretical understanding of the relationship between apology and forgiveness in the RJ processes. After identifying key elements and impediments of the apology–forgiveness cycle during RJ meetings based on the existing literature, we develop a theoretical model of the apolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…Furthermore, recently, scholars found that a wrongdoer’s apology is perceived as more sincere when combined with a reparation offer, as opposed to a mere verbal apology (Jeter & Brannon, 2018; Suzuki & Jenkins, 2022). In this study, the expression of accountability shifted the narrative of the harm from responsibility for past actions to accountability for future ones.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recently, scholars found that a wrongdoer’s apology is perceived as more sincere when combined with a reparation offer, as opposed to a mere verbal apology (Jeter & Brannon, 2018; Suzuki & Jenkins, 2022). In this study, the expression of accountability shifted the narrative of the harm from responsibility for past actions to accountability for future ones.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of theoretical understanding of the relationship between apology and forgiveness in the RJ processes. After identifying key elements and impediments of the apology-forgiveness cycle during RJ meetings based on the existing literatures, we develop a theoretical model of the apology-forgiveness cycle during RJ encounters (Suzuki, & Jenkins, 2022). Indonesia adheres to a retributive punishment system, namely a criminal justice system with a focus on sentencing as a form of retribution for the perpetrator's actions and as a means of preventing similar crimes.…”
Section: B Research Methodsmentioning
confidence: 99%
“…Last but not least, forgiveness may also serve as an enabling factor for victim recovery in restorative justice. Although forgiveness is not frequently discussed in the restorative justice literature due to its perception as a secondary goal that should be offered by victims out of their generosity (Armour & Umbreit, 2018; Suzuki & Jenkins, 2023), forgiveness may be offered more often in restorative justice than previously recognized (e.g., see the review by Suzuki & Jenkins, 2022). This prevalence may be because even victims of violence sometimes participate in the restorative justice process with a pro-social motive to support the rehabilitation of justice-involved persons (Van Camp & Wemmers, 2013).…”
Section: A Theoretical Framework For the Victim Recovery Process In R...mentioning
confidence: 99%
“… 1. Although an apology from people who offend has the potential to foster forgiveness among victims in restorative justice, it is worth noting that victims may also express forgiveness even in the absence of such apologies (for more details, see Suzuki & Jenkins, 2023). Consequently, I consider forgiveness as a distinct enabling factor for the victim recovery process in restorative justice. …”
mentioning
confidence: 99%